Citizen science benefits coral reefs and community members alike - Hesley, Dalton; Kaufman, Madeline; Lirman, Diego (Frontiers in Environmental Science, 2023)
The field of coral gardening and active restoration has expanded rapidly over the past 2 decades in response to the rapid, global decline of coral reefs. Even with this expansion, the long-term success of coral restoration and ecosystem recovery will still depend on social action to mitigate the local and global stressors plaguing reefs. Rescue a Reef (RAR), a citizen science program, was designed to engage community members and catalyze action through hands-on, experiential opportunities as coral gardeners and restoration practitioners alongside trained scientists. While community-based coral restoration programs can be a powerful platform for education and increase project success, few programs utilize citizen science and even fewer measure and evaluate the long-term impacts of these activities. Here, we describe the benefits of citizen science for coral conservation identified through a mixed methods longitudinal evaluation of RAR after 8 years of citizen science programming. A survey was distributed to all program participants and responses were compared to historical pre-post survey responses of citizen scientists as well as to a control group. We found that despite the passing of time, citizen scientists largely retained their knowledge levels on coral reef-related topics and were significantly more knowledgeable on the topics than a control group. Additionally, RAR successfully developed a strong sense of community, coral stewardship, and program support among its participants. Most importantly, citizen science has the potential to act as a vehicle for positive social change with the majority of participants reporting changes in perceptions (70.5%) and behavior (60.1%) because of their participation in RAR. Thus, the untapped potential of citizen science as a tool for coral reef conservation, restoration, and stewardship must be realized. Furthermore, citizen science projects must embed evaluation in their activities to gather information and evidence on the effectiveness of their activities as well as potential areas for improvement.